Eight Thousand Years of Maltese Maritime History : Trade, Piracy, and Naval Warfare in the Central Mediterranean - Atauz, Ayse Devrim (Book collections on Project MUSE., 2008)
Offering a general overview of essential facts, including geographical and oceanographic factors that would have affected the navigation of historic ships, major relevant historical texts and documents, the logistical possibilities of ancient ship design, a detailed study of sea currents and wind patterns, and especially the archaeological remains (or scarcity thereof) around the Maltese maritime perimeter, the author argues that Malta mattered far less in maritime history than has been previously asserted.